2022
DOI: 10.1039/d1cy02226a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic cracking of CH3Cl on copper-based phases

Abstract: The methylchlorosilanes synthesis from Si and CH3Cl, also called the direct synthesis suffers from a side-reaction during which the CH3Cl reactant cracks and forms carbonaceous compounds, called coke. It leads...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Experiments show that metallic copper catalyzes the cracking reaction . While it is shown that Cu can be converted to CuCl when reacting with CH 3 Cl at lab-scale, it is also known that stable Cu 0 is formed during the reaction. , From their results, Blaser et al. suggest that coke can reduce the CuCl and thus deactivate copper as catalyst for the direct synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Experiments show that metallic copper catalyzes the cracking reaction . While it is shown that Cu can be converted to CuCl when reacting with CH 3 Cl at lab-scale, it is also known that stable Cu 0 is formed during the reaction. , From their results, Blaser et al. suggest that coke can reduce the CuCl and thus deactivate copper as catalyst for the direct synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…6 While it is shown that Cu can be converted to CuCl when reacting with CH 3 Cl at lab-scale, 6 it is also known that stable Cu 0 is formed during the reaction. 6,12 From their results, Blaser et al suggest that coke can reduce the CuCl and thus deactivate copper as catalyst for the direct synthesis. At the same time experimental results indicated that CH 3 cracking may initiate at elemental Cu.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations